Scientometric Dimensions of the Nuclear Physics Division at Bhabha Atomic Research Centre - Upadhye, Rekha P.; Kademani, B. S.; Surwase, Ganesh; Kumar, Vijai (Journal of Information and Knowledge, 2014)
This Scientometric study analyses the publications of Nuclear Physics Division at Bhabha Atomic Research Centre. There were 257 research papers published during 2003-2008 in diverse domains of nuclear physics: Nuclear Reactions and Spectroscopy (78), High Energy Physics and Quark Gluon Plasma (58), Interdisciplinary Research and Applications (29), Intermediate Energy Reactions (27), Theoretical Research (23), Nuclear Fission (22), Detectors and Nuclear Instrumentation (14) and Accelerators and Instrumentation (6). The highest number of publications (51) was in the year 2006. The average number of publications per year was 42.83. The most prolific authors were: Choudhury R.K. (81), Mohanty A.K. (60), Dutta D. (57) and Kailas S. (45). The publications of Nuclear Physics Division were spread over 42 journals. The leading journals preferred by the scientists of Nuclear Physics Division were Physical Review- C with 75 publications, Physical Review Letters with 38 publications, Nuclear Physics- A with 22 publications, Pramana - Journal of Physics with 18 publications, European Physical Journal- A with 11 publications and Physics Letters- B with 10 publications. Collaboration trend was mega-authored publications. There were more than 70 % mega-authored publications.